COMBINING ABILITY AND GENETIC PARAMETERS FOR YIELD AND ITS COMPONENETS USING LINE X TESTER ANALYSIS IN SUMMER SQUASH - Zhiyan A. T,; Mohammed A. Hussain, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to investigate combining ability and genetic parameters in summer squash (cucurbita pepo L.). Eight inbred lines of summer squash were crossed in line x tester method in summer season 2020. The parental lines (3 tester and 5 lines) and their off springs (15 hybrids) were planted out in the summer season  2021 at vegetable field, Horticulture Department, College of Agricultural Engineering Science, Duhok University. The experiment lay out using randomized complete block design with three replications. The results indicated that the mean square for genotypes were highly significant effect for tester , line and line x tester in all studied traits. The Tester LBL2 and line PEP1670 were the best combiner for days to 50% female flowering, number of fruit plant-1 and yield kg plant-1. The crosses (LBL2 X N33133) and (LES3 X CNS2881)  exhibited significant positive effect of specific combining ability for fruit length cm, number of fruit plant-1 and yield plant-1. The heritability in broad sense were higher than narrow sense heritability for all studied traits ranged between 93% for days to 50% female flowering to 40% for fruit weight. The average degree of dominance less than one in all traits except days to 50% female flowering and fruit length.